ANALISIS STILISTIKA DAN NILAI PENDIDIKAN KARAKTER KUMPULAN PUISI PERIHAL GENDIS SERTA PEMANFAATANNYA DALAM PEMBELAJARAN SASTRA - Mahmudah, Mar'atul Dini Latif; Waluyo, Herman J; Saddhono, Kundharu (Universitas Sebelas Maret, 2020)
This research study aims to describe and explain (1) the diction of poems collection entitled Perihal Gendis by Sapardi Djoko Damono; (2) the figurative language of poems collection entitled Perihal Gendis by Sapardi Djoko Damono; (3) the imagery of poems collection entitled Perihal Gendis by Sapardi Djoko Damono; (4) character education values of poems collection entitled Perihal Gendis by Sapardi Djoko Damono; and (5) the stylistic relevance of poems collection entitled Perihal Gendis by Sapardi Djoko Damono by learning to write poems in Senior High School.This research used a qualitative descpriptive method literature with content analysis. The source of data of this study is poems book and collection entittled Perihal Gendis by Sapardi Djoko Damono published by Gramedia Pustaka Utama. This technique is content analysis method. The data validation used in this study is triangulation source of data and theory. The results of this study as follows : (1) the connotative meanings of diction are more dominant than denotative; (2) the figurative languages are found out that the top three most dominant are Anaphora then Personification. The simbolik; (3) the use of varied imageries are found out that the dominant imagery is motion image; (4) The most dominant value of character education is curiosity; (5) This poems book and collection can be evaluated to poetry writing materials in Senior High School.